Preparation of Zinc Oxide Nano-Layer on Cotton Fabric for UV Protection Application - Sharouf, Hoda Mohammad; Tuhmaz, Ghazal; Saffour, Ziad (Al-Nahrain Journal for Engineering Sciences, 2019)
Zinc oxide nano particles is one of the best choices for ultraviolet protection due to its special properties. In this research, the UV-protection ability of sol gel-derived thin ZnO films on cotton fabrics was investigated. Various polymers have been used as adhesives to bind the nano-oxide with the surface of the treated fabric. Scanning electron microscopy and UV spectroscopy were carried out to study the properties of the treated fabrics. The results showed that the diameters of the synthesis zinc oxide particles - (68.81, 41.76 and 44.6 nm) with (PVA, PVP and CMC) respectively- were of the nanostructure, and the smallest diameter of the particles was produced with polyvinylpyrrolidone as adhesive. Using a spectrophotometer showed a decrease in the transmittance of the studied samples compared with the raw untreated sample of about 23%.